The efficiency of monopolistic provision of public goods through simultaneous bilateral bargaining - Noriaki Matsushima; Ryusuke Shinohara (Osaka University, Institute of Social and Economic Research (ISER), 2015)
We examine a monopolistic supplier's decision about a pure public good when he/she must negotiate with beneficiaries of the good. In our model, while the level of the public good is decided unilaterally by the supplier, the cost share of the public good is negotiated between the supplier and beneficiaries. Our bargaining model is built on simultaneous bilateral bargaining and the bargaining power of the supplier is a key factor for the analysis. We show that under some mild conditions, the supplier produces the public good at a Pareto-efficient level in equilibrium if and only if his/her bargaining power is sufficiently weak. In addition, under some reasonable parametric functions, we show that the equilibrium likelihood of the efficient provision of the public good diminishes as the number of beneficiaries increases. We show by a numerical example that the source of the inefficient provision of the public good when the supplier's bargaining power is sufficiently strong may be the excessive supply of the public good.
Keywords: C78; D42; H41; H44; 330; Public good; Simultaneous bilateral bargaining; Supplier bargaining power; Nash bargaining solution